Glucose metabolism in the erythrocytes of the buffalo (Bubalus bubalis) - Cesar, M. D.; Fernandes, L. C.; Curi, R.; Sassaki, K. T.; Rosa, C. D.; Rosa, R. (Elsevier B.V., 1997)
(CO2)-C-14 production from [1-C-14] glucose, the rate of glycolysis measured by the value of lactate production and the activities of various enzymes were determined in buffalo erythrocytes. Buffalo red cell glycolytic metabolites were estimated and used for the calculation of the mass action ratios of reactions catalyzed by the glycolytic enzymes of Bubalus bubalis. A comparison of the values of the mass action ratios with the equilibrium constants of the various glycolytic reactions indicate that hexokinase, phosphofructokinase, phosphoglycerate kinase and pyruvate kinase reactions are displaced from equilibrium, suggesting a regulatory role for each of these enzymes in buffalo erythrocyte glycolysis. (C) 1997 Elsevier B.V.
Keywords: Buffalo erythrocytes; lactate production; glycolysis; pentose phosphate pathway; glucose; hexokinase; phosphofructokinase; pyruvate kinase